REFLEKSI PESERTA DIDIK TERHADAP PEMBELAJARAN BERBASIS DIGITAL - Amarulloh, Adhitya; Surahman, Endang; Meylani, Vita (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2019)
Digitalization is the main characteristic of 21st century, today is knowns as information society. Distribution of information more rapidly and affecting social life, it also affects education system. Digitalization of Education growth rapidly, and it does affect student as well. This research applied survey research method with design that used cross-sectional studies, the population are student of SMA Negeri 2 Tasikmalaya school year of 2018th/2019th, sampling with cluster random sampling. Data collection through questionnaire, unstructured interview and observation, validity checking with method triangulation and data analyzing with descriptive analyzing. The result is, student being addicted with technology proved by the uses of smartphone is in high percentage and the duration of smartphone uses is also high it makes student being familiar with digital world. Meanwhile if it’s being correlated with education needed, the student lack of understanding with the beneficial of technology in education as well as learning. In fact, student being skeptic and not welcoming digitalization in learning. To build positive paradigms digital learning in student, teacher must have selected with using learning application and controlling the process of learning to prevent the unwanted things